The complex amino acid diet of Francisella in infected macrophages - Barel, Monique; Ramond, Elodie; Gesbert, Gael; Charbit, Alain (Frontiers in Cellular and Infection Microbiology, 2015)
Francisella tularensis, the agent of the zoonotic disease tularemia, is a highly infectious bacterium for a large number of animal species and can be transmitted to humans by various means. The bacterium is able to infect a variety of cell types but replicates in mammalian hosts mainly in the cytosol of infected macrophages. In order to resist the stressful and nutrient-restricted intracellular environments, it encounters during its systemic dissemination, Francisella has developed dedicated stress resistance mechanisms and adapted its metabolic and nutritional needs. Recent data form our laboratory and from several other groups have shown that Francisella simultaneously relies on multiple host amino acid sources during its intracellular life cycle. This review will summarize how intracellular Francisella use different amino acid sources, and their role in phagosomal escape and/or cytosolic multiplication and systemic dissemination. We will first summarize the data that we have obtained on two amino acid transporters involved in Francisella phagosomal escape and cytosolic multiplication i.e. the glutamate transporter GadC and the asparagine transporter AnsP, respectively. The specific contribution of glutamate and asparagine to the physiology of the bacterium will be evoked. Then, we will discuss how Francisella has adapted to obtain and utilize host amino acid resources, and notably the contribution of host transporters and autophagy process in the establishment of a nutrient-replete intracellular niche.